2017
DOI: 10.1002/ecs2.2036
|View full text |Cite|
|
Sign up to set email alerts
|

Both canopy and understory traits act as response–effect traits in fire‐managed forests

Abstract: Citation: Refsland, T. K., and J. M. Fraterrigo. 2017. Both canopy and understory traits act as response-effect traits in fire-managed forests. Ecosphere 8(12):e02036. 10. 1002/ecs2.2036 Abstract. Community-level shifts in the distributions of plant functional traits associated with environmental change are expected to influence ecosystem functioning. However, few studies have identified traits that both respond to environmental change and affect ecosystem properties, thus limiting potential to scale the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In our study, community aggregated traits included LCC, LDMC, LNC, PH, and SLA. Considering these functional traits are highly related to the light‐capturing capacity, photosynthetic rate and growth rate (Meers et al., ; Refsland & Fraterrigo, ; Sabatini et al., ), our study suggested that understory productivity was higher in communities composed of species with traits on the fast‐growth end of the leaf economics spectrum (Reich, ). In contrast, we found functional diversity (FDis), representing multiple trait axes, did not affect UABP.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In our study, community aggregated traits included LCC, LDMC, LNC, PH, and SLA. Considering these functional traits are highly related to the light‐capturing capacity, photosynthetic rate and growth rate (Meers et al., ; Refsland & Fraterrigo, ; Sabatini et al., ), our study suggested that understory productivity was higher in communities composed of species with traits on the fast‐growth end of the leaf economics spectrum (Reich, ). In contrast, we found functional diversity (FDis), representing multiple trait axes, did not affect UABP.…”
Section: Discussionmentioning
confidence: 72%
“…There are a large number of potentially related traits for a given ecosystem process (Pérez‐Harguindeguy et al., ). We selected six functional traits for all recorded understory species, which are closely related to understory light capture, resource utility, growth, and productivity (Meers, Kasel, Bell, & Enright, ; Refsland & Fraterrigo, ; Sabatini et al., ). Specifically, leaf area (LA, mm 2 ) is related to species' ability to capture light resources, which affects the photosynthetic rate.…”
Section: Methodsmentioning
confidence: 99%
“…For example, on a given focal niche axis, the idea that variable performance of narrow NB species would translate into variable ecosystem functioning in changing environments (discussed above) seems most applicable when the traits that respond to the environment and that shape NB ("response" traits) also drive ecosystem functioning ("effect" traits; Lavorel and Garnier 2002). However, the overlap between these response and effect traits remains an area of active research (Funk et al 2017;Refsland and Fraterrigo 2017). Ecosystem functioning depends on the relative abundances of effect traits, so we envision two general pathways by which traits, NB, and ecosystem functioning interact.…”
Section: Niche Breadth and Biodiversity-ecosystemmentioning
confidence: 99%
“…Understory vegetation is thought to play a key role in carbon dynamics of ecosystems across the globe. Uncertainties exist, however, regarding the total carbon found in this vegetation strata (Johnson et al 2017, Refsland andFraterrigo 2017), and these uncertainties are expected to increase as climatic extremes become more common and severe (IPCC 2014). These shifts in climate, particularly drought, will have a direct effect on ecosystem structure (both understory and overstory), function (phenology and physiology), and ultimately their management strategies (Rich et al 2008, Becknell et al 2015.…”
Section: Introductionmentioning
confidence: 99%